Novel Approach for Real-time Simulation of Power Electronic Circuits Comprising Fast FPGA-based Output Models - Kiffe, Axel; Brose, M.; Schulte, Thomas (International Exhibition & Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM Europe 2013))
Hardware-in-the-loop simulation of power electronic devices is growing in importance in diverse fields. For testing the electronic control units in automotive applications hardware-in-the-loop simulation is a today's standard method. It is also applied for many industrial applications like power converters and electric drives. Anyway real-time capable models of power electronics are required. In this contribution a novel approach is presented, which applies simplified and FPGA-based output models for significantly improving the feedback dynamics of a hardware-in-the-loop simulation of power electronic devices.